Peningkatan Hasil Tanaman Okra Dengan Pemberian Pupuk Kompos dan NPK - Made Sri Yuliartini; Ketut Agung Sudewa; Luh Kartini; Ersa Remi Praing (GEMA AGRO, 2018)
The purpose of this research is to determine the effect of compost and NPK Phonska fertilizer application to the growth and yield of okra plants, and to get optimum dose. This research was conducted in experimental garden of Agricultural Faculty of Warmadewa University. The design used in this research is factorial randomized block design (RAK) consisting of two treatments: compost fertilizer and NPK Phonska fertilizer. The interaction treatment between doses of compost fertilizer with NPK Phosnka and single treatment of NPK Phonska have no significant effect on all observed variables. The treatment of compost fertilizer dosage have no significant to effect foe leaf number and dry weight of oven fruit, but it had significant effect to the weight of fresh and dried weight of oven stover and very significant effect on the variables of plant height, the number of fruit and the weight of fresh fruit. The dosage of compost fertilizer 8 ton ha-1 to got the highest fresh weight of fruit per plant which is 380,42 g, an increase of 44,05% if compared with the lowest fresh fruit weight per plant obtained in the treatment without compost 0 tons ha- Ë¡ of 264.08 g. The results of the distribution of NPK Phonska at different doses have no significant effect on one another . However, , the highest fresh fruit weight was obtained at NPK treatment at 400 kg ha-1 treatment ie 351,75g. This increased by 7.02% when compared with the freshest weight of lowest fruit obtained at 200 kg ha-1 treatment ie 328,67 g.